NAD+ Metabolism as an Emerging Therapeutic Target for Cardiovascular Diseases Associated With Sudden Cardiac Death - Xu, Weiyi; Li, Le; Zhang, Lilei (Frontiers in Physiology, 2020)
In addition to its central role in mediating oxidation reduction in fuel metabolism and bioenergetics, nicotinamide adenine dinucleotide (NAD+) has emerged as a vital co-substrate for a number of proteins involved in diverse cellular processes, including sirtuins, poly(ADP-ribose) polymerases and cyclic ADP-ribose synthetases. The connection with aging and age-associated diseases has led to a new wave of research in the cardiovascular field. Here, we review the basics of NAD+ homeostasis, the molecular physiology and new advances in ischemic-reperfusion injury, heart failure, and arrhythmias, all of which are associated with increased risks for sudden cardiac death. Finally, we summarize the progress of NAD+ boosting therapy in human cardiovascular diseases and the challenges for future studies.